An evaluation of the interior design of selected restaurant-bars in Quezon City in their compliance with the Tobacco Regulation Act of 2003 - Orejo, Jhessa Marie S. (College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT Five restaurant-bars in Quezon City were studied in order to evaluate whether their interiors were compliant with the Philippine RA 9211 or the Tobacco Regulation Act of 2003, which regulates the packaging, use, sale, distribution and advertisement of tobacco products. The samples were chosen through quota sampling. This study is a multiple case study wherein design elements in the smoking areas of the samples were identified and compared with the guidelines of the RA 9211. Methods of gathering data includes thorough observation and photo documentation. An observation guide was used to objectively record data. The data collected were presented in two parts - per restaurant bar, and the comparison of all samples in terms of the guidelines in the law. the layout of the space, type of door used, materials and finishes present, and accessories used were given importance. Results fro the study showed that none of the selected restaurant-bars were able to observe all the guidelines stipulated in the law with regards to the design of smoking areas. Failure to use the required signage in the smoking areas and non-smoking areas was the leading cause why the samples were not able to fully observe the law. Other aspects that are related to secondhand smoke leakage and thirdhand smoke like space layout, type of door, materials, finishes and accessories used were not considered by some of the samples as none of the samples showed 100% consideration of environmental tobacco smoke. Findings also suggest that the government is not strict in implementing the said law, and that the provisions of the said law are not enough to protect the non-smokers from the dangers of tobacco smoke, thus reinforcement and improvement of the law is needed. Furthermore, more research is needed on the reactions to smoke among different interior finishing materials.